The vitamin D3 axis in laryngeal cancer: a double-edged sword modulated by estrogen signaling - Guo, Qian; Chen, Yicheng; Zhou, Qiang; Dong, Dong; Huang, Shuman; Shan, Meirong; Zhang, Baiquan; Pan, Liuye; Zhao, Yulin (Frontiers in Immunology, 2025)
Laryngeal cancer remains a formidable clinical challenge, with growing evidence that vitamin D3 acts as a potential therapeutic modulator. However, its precise role is complex, largely due to poor understanding of the mechanisms underlying its variable efficacy. This review synthesizes current knowledge to establish a comprehensive framework for vitamin D3’s dichotomous role in laryngeal carcinogenesis. First, we clarify its two distinct mechanisms of action: (i) directly inhibiting laryngeal cancer cell proliferation and survival via the canonical vitamin D receptor (VDR) axis—triggering G0/G1 cell cycle arrest, inducing apoptosis, and reversing epithelial-mesenchymal transition (EMT); (ii) indirectly exerting anti-tumor effects by reprogramming the tumor immune microenvironment, including enhancing cytotoxicity of CD8+ T and natural killer (NK) cells, promoting dendritic cell maturation, and suppressing key inflammatory pathways such as the COX-2/PGE2 axis. Subsequently, we propose that the net effect of vitamin D3 signaling is context-dependent and double-edged, determined mainly by host-intrinsic and viral factors—most notably estrogen receptor α (ERα66) expression. Specifically, vitamin D3-related products promote cell growth in ERα66-positive laryngeal cancer cell lines, but suppress growth in ERα66-negative lines, thereby aiding cancer therapy. This integration provides a nuanced paradigm, highlighting the need for biomarker-driven patient stratification to harness vitamin D3’s therapeutic potential in laryngeal cancer.